Österreichische Entwicklungspolitik 2021. COVID-19 and the Global South – Perspectives and Challenges - Österreichische Forschungsstiftung für Internationale Entwicklung (ÖFSE) (Südwind-Verlag, 2021)
This year's issue is devoted in its thematic section to the impact of the COVID-19 pandemic on the Global South. The pandemic has hit developing countries particularly hard. Income losses, impoverishment and rising inequality, overburdened health systems and a regression in education participation are only the first perceptible impacts. Medium- to long-term implications of the pandemic for the Global South, for example with regard to the worsening financial and debt situation or changing global production patterns (as induced e.g. by digitalisation or the reorganization of supply chains), are not yet easy to assess, but are in part worrying. Development policy and development cooperation must try to counteract these dynamics. The second part of the publication analyses Austria's overall financial flows to developing countries. The third part of the publication provides a chronological overview of selected important events, decisions and statements in the field of development policy and development cooperation in 2020 and the first half of 2021. – – Die Ausgabe 2021 der Publikation widmet sich in ihrem thematischen Teil den Auswirkungen der COVID-19 Pandemie auf den Globalen Süden. Die Pandemie hat die Entwicklungsländer besonders hart getroffen. Einkommensverluste, Verarmung und steigende Ungleichheit, überlastete Gesundheitssysteme und ein Rückfall bei der Bildungsbeteiligung sind nur erste wahrnehmbare Auswirkungen. Mittel- bis langfristige Implikationen der Pandemie auf den Globalen Süden, etwa im Hinblick auf die sich verschlechternde Finanz- und Verschuldungssituation oder sich verändernde globale Produktionsmuster (Stichworte Digitalisierung bzw. Reorganisation von Lieferketten), sind heute noch nicht gut abschätzbar, zum Teil aber besorgniserregend. Entwicklungspolitik und Entwicklungszusammenarbeit müssen versuchen, diesen Auswirkungen entgegenzusteuern. Der zweite Teil analysiert und interpretiert die Finanzflüsse Österreichs an Entwicklungsländer. Abschließend liefert die Chronik der Entwicklungspolitik und Entwicklungszusammenarbeit einen Überblick über wichtige Ereignisse im Zeitraum 1.1.2020 bis 30.6.2021.
Keywords: 330